Peran Penyuluh Pertanian dalam Pemberdayaan Kelompok Tani (Studi Kasus Kelompok Jangkat Raya Mandiri di Desa Jangkat Kabupaten Musi Rawas Utara) - Yoga Prayoga (Greenation Publisher & Yayasan Global Research National, 2023)
Abstract: The aims of this study were (1) to describe the role of agricultural extension workers in attacking fertile farmer groups. (2) Knowing the effect of the role of agricultural extension agents on the empowerment of Subur farmer groups. The analysis used is the first analysis of qualitative data to describe the role of agricultural extension workers in empowerment, the second uses the questionnaire method, namely a number of written questions used to obtain information from respondents in report articles about their personalities or things that are known and that are third simple regression analysis to determine the effect of the role of agricultural extension workers in empowering Subur Farmer Groups. Based on the research results, it can be concluded that the role of agricultural extension workers as motivators, facilitators, and educators is quite good in the process of playing Subur Farmer Groups, and the role of agricultural extension workers as motivators, facilitators, and educators has a significant effect on the empowerment of Subur Farmer Groups, namely a significant value of 0.003 < 0.05 (predetermined standard error) through the results of simple regression analysis. Abstrak: Tujuan dari penelitian ini adalah (1) Mendeskripsikan peran penyuluh pertanian dalam upaya memberdayakan kelompok tani subur. (2) Mengetahui pengaruh peran penyuluh pertanian terhadap keberdayaan kelompok tani Subur. Analisis yang di gunakan adalah yang pertama analisis data kualitatif untuk mendeskripsikan peran penyuluh pertanian dalam pemberdayaan, yang kedua menggunakan metode Angket (kuisioner) yaitu sejumlah pertanyaan tertulis yang digunakan untuk memperoleh informasi dari responden dalam arti laporan tentang pribadinya atau hal-hal yang diketahui dan yang ketiga analisis regresi sederhana untuk mengetahui pengaruh peran penyuluh pertanian dalam pemberdayaan Kelompok Tani Subur. Berdasarkan hasil Penelitan dapat di simpulkan bahwa peran penyuluh pertanian sebagai motivator, fasilator, dan edukator sudah cukup baik dalam proses memberdayakan Kelompok Tani Subur, dan peran penyuluh pertanian sebagai motivator, fasilitator, dan edukator berpengaruh secara signifikan terhadap keberdayaan Kelompok Tani Subur yakni nilai signifikan 0.003 < 0,05 (standar eror yang telah ditentukan) melalui hasil analisis regresi sederhana.